Effects of nanoencapsulated essential oil blend in diet of Lohmann Brown hens on posture percentage, quality and egg oxidative stability - Gilmar Mendoza–Ordoñez; Miguel Callacná–Custodio; Vanessa Armas–Azabache; Bruno Loyaga–Cortéz; Roberto Ybañez–Julca; Daniel Asunción–Alvarez; Hugo Saavedra–Sarmiento; Aníbal Rodriguez–Vargas (Revista Científica)
Essential oils have demonstrated beneficial effects on the productive parameters of poultry. However, the impact of nanoencapsulated essential oil blends (N–EOs) in the diet of laying hens has been little described. The objective of the research was to evaluate the effect of mixtures of N–EOs in diets of Lohmann Brown hens on the percentage of laying, quality, and oxidative stability of the egg product. 600 birds were randomly distributed into five groups (n=150 per group), according to a completely randomized design, receiving the control group (T0) a conventional diet without N–EOs while the experimental groups received mixtures of N–EOs based on soursop (S), lemon (L) and eucalyptus (E) in different proportions: T1 (S: 33.4 , L:33.3%, E:33.3%), T2 (S:50%, L:25%, E:25%), T3 (S:25%, L:50%, E:25%) and T4 ( S:25%, L:25%, E:50%). The results showed that the T4 group showed the highest posture rate compared to the T2 and T3 groups (P<0.05), although it was similar to T0 and T1. Comparatively, the feed conversion was better in the T4 treatment compared to T0 (P<0.05). The analysis of egg quality showed that the T1 and T2 treatments reached a greater shell thickness (mm) compared to the group with conventional diet (P<0.05). The oxidative stability of the egg yolk evaluated through the levels of malondialdehyde (MDA), showed that both the T1 and T4 groups had lower levels of MDA (P>0.05) compared to the standard diet (T0). In conclusion, diets with N–EOs constitute a promising option that favors feed conversion, laying percentage, and greater shell thickness of the eggs of laying hens.